Preparation of Au-Doped Two-Phase TiO2 Nanoparticles by One-Step Method as Photocatalytic Applications - Neama, Rasha Jameel; Alosfur, Firas Kamel Mohamad; Tahir, Khawla Jemeal; Ridha, Noor Jawad; Ahmed, Luma Majeed (Universitas Gadjah Mada, 2024)
The synthesis of pure TiO2 and X% Au/TiO2 NPs was achieved via a sol-gel technique. The influence of Au concentration on structural, morphological, and optical features, as well as photocatalytic activity, was studied. XRD analysis revealed the presence of crystallized titanium consisting of anatase and rutile phases. The surface composition and electronic structure of TiO2 and X% Au/TiO2 catalysts were investigated using XPS analysis. Au/TiO2 consists of Ti 2p, O 1s, and Au 4f regions from XPS analysis. FESEM and TEM were utilized to analyze the morphology of the samples. FTIR spectrum indicated the presence of OH, CH2, and Ti–O–Ti groups in TiO2 samples, with an additional peak at 2108.89 cm−1 indicating the presence of gold in X% Au/TiO2 samples. The specific surface area increased from 33.36 m2/g for pure TiO2 to 51.62 m2/g after the doping of 2.5% Au NPs. The incorporation of Au on the TiO2 surface significantly influenced the optical properties in the 490 to 590 nm region, observed through the UV-vis absorption spectrum. The 2% Au/TiO2 NPs exhibited higher catalytic activity than pure TiO2, degrading methylene blue dye by 72.43% within 120 min.